PENGARUH KOMPETENSI, BUDAYA KERJA, DAN PEMBERIAN REMUNERASI TERHADAP KINERJA PEGAWAI PADA KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM SULAWESI TENGGARA - Suarni Suarni; Buyung Sarita; Patwayati Patwayati (Pascasarjana Universitas Halu Oleo, 2020)
The purpose of this study was to examine and analyze the effect of employee competence, work culture, and remuneration on employee performance at the Regional Office of the Ministry of Law and Human Rights, Southeast Sulawesi. This research approach is a survey with explanatory research design. The data was collected using an instrument in the form of a questionnaire. The population of this research is all employees who have become Civil Servants (PNS) of the Regional Office of the Ministry of Law and Human Rights in Southeast Sulawesi. The sample size was determined using the Taro Yamane formula, so that a sample of 100 respondents was obtained. The analytical tool used is the Multivariate Regression Analysis with the SPSS program package.The results showed that competence, work culture and remuneration simultaneously and racially had a positive and significant effect on improving employee performance at the Regional Office of the Ministry of Law and Human Rights in Southeast Sulawesi. Contribution of the influence of competence, work culture and remuneration is shown by the value ( ) of 79.2% and the remaining 20.8% is influenced by other variables outside the research model. This means that the ability of competence, work culture and remuneration have a very big influence on employee performance.